2006
DOI: 10.1055/s-2005-916220
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Tetrahydrofuran- and Dihydrofuran-Type Lignans from the Stem ofBeilschmiedia tsangii

Abstract: Five new compounds including two tetrahydrofuran-type lignans, beilschmin A and beilschmin B, a dihydrofuran-type lignan, beilschmin C, and two 1-phenylbutyl benzoates, tsangin A and tsangin B, together with thirteen known compounds have been isolated from the stem of Beilschmiedia tsangii. The structures of these new compounds were determined through spectral analyses. Among the isolates, beilschmin A (1), beilschmin B (2), beilschmin C (3), tsangin A (4), tsangin B (5), 2,6,11-trimethyldodeca-2,6,10-triene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 12 publications
(15 reference statements)
1
62
1
Order By: Relevance
“…17 These isolated compounds were found for the first time in this plant. There are several reports on lignans neolignans isolated from the Beilschmiedia species, such as B. tsangii, 9 B. volckii, 21 and B. kunstleri.…”
Section: β-Sitosterol (8)mentioning
confidence: 96%
“…17 These isolated compounds were found for the first time in this plant. There are several reports on lignans neolignans isolated from the Beilschmiedia species, such as B. tsangii, 9 B. volckii, 21 and B. kunstleri.…”
Section: β-Sitosterol (8)mentioning
confidence: 96%
“…[47]. Chen et al [50] studied the in vitro cytotoxicity of several compounds isolated from B. tsangii. They found that tsangin A-B, α-tocospiro B and beilschmin A displayed from medium to strong activity against the P-388 (murine leukemia cell) line.…”
Section: Cytotoxicity Activitymentioning
confidence: 99%
“…The known isolates were readily identified by a comparison of physical and spectroscopic data (UV, IR, 1 H NMR, [D] D , and MS) with corresponding authentic samples or literature values, and this included two amides, N-trans-feruloyltyramine (2) [13] and N-trans-feruloyloctopamine (3) [14], a benzenoid, vanillin (4) [15], a benzoquinone, D-tocopheryl quinone (5) [16], and three steroids, E-sitostenone (6) [17], E-sitosterol (7) [18], and 6D-hydroxystigmast-4-en-3-one (8) [8].…”
mentioning
confidence: 99%